IMPLEMENTASI KEWAJIBAN PRASARANA, SARANA, DAN UTILITAS UMUM OLEH PENGEMBANG DALAM PERSPEKTIF PERLINDUNGAN KONSUMEN: Implementation of Infrastructure, Facilities, and Public Utilities Obligations by Developers in The Perspective of Consumer Protection - Samuel Christian; Renti Maharaini Kerti (Faculty of Law, Universitas Trisakti, 2025)
Based on Law No. 1 of 2011, Government Regulation No. 12 of 2021, Minister of Home Affairs Regulation No. 9 of 2009, Bogor Regency Regional Regulation No. 7 of 2012, Bogor Regent Regulation No. 7 of 2012 regulates Infrastructure, Facilities, and Public Utilities (PSU) in housing and residential areas, one of which is the submission of PSU from developers to local governments. The issues raised are how the implementation of the provisions of Infrastructure, Facilities, and Public Utilities in Cluster Pasadena Sentul City Housing and the efforts of the housing office if the developer has not implemented these provisions. The author uses normative research methods with descriptive analysis and the type of data using secondary data supplemented by primary data. This research uses qualitative analysis research and deductive inference from general to specific. The results and conclusions of the article, namely the implementation of the PSU submission provisions pursued by the Bogor Regency DPKPP are needed to ensure that developers comply with regulations. Developers who do not submit PSUs to the local government can be subject to administrative and criminal sanctions. It aims to protect consumer rights, so that they can enjoy a decent residential environment without undue cost burden.